Conference Wrap Up - Organizers, Conference (Prentice Hall, 2007)
This is a wrap up of the conference with all of the speakers on the ast day of the conference, December 6th, 2007.
Online resource; Title from title screen (viewed December 6, 2007)
Keywords: Electronic videos